Trunk Posture Exposure Patterns among Prairie Ranch and Grain Farmers. Issue 2 (2nd April 2020) - Khan, Muhammad Idrees; Bath, Brenna; Kociolek, Aaron; Zeng, Xiaoke; Koehncke, Niels; Trask, Catherine
ABSTRACT: Objectives : Low back disorders (LBD) are the most common musculoskeletal disorder among farmers, and awkward trunk postures such as repetitive bending are often cited as a contributor. However, it is not clear whether trends of increasing mechanization in agriculture may be impacting the requirement for trunk-intensive tasks. This study compared the patterns of working trunk posture among prairie farmers during both machine-intensive and non-intensive work days. Methods : Forty-nine adult farm workers from 22 farms participated in this study. Individual and farm characteristics were documented via questionnaire. Trunk angles and velocities were measured with an I2M inertial sensor placed on the chest. Participants completed electronic posture assessments during up to three regular work days throughout the growing season for a total of 91 electronic posture measurements. Forward and lateral trunk bending patterns were expressed in three domains: magnitude, duration, and frequency. Results : Working tasks were categorized into driving, manual, and mixed. Driving was the most commonly measured task (52% of work days), and mixed tasks the least (12%). Both 90th percentile trunk flexion-extension angles and velocities were significantly higher for manual as compared to driving tasks. Participants spent 38% of their working time in trunk forward flexion ≥ 20°, which, according to previous epidemiological studies, may increase their risk for LBD. Conclusion : The directly-measured trunk posture exposure patterns in this study suggest that machinery-intensive workdays result in less awkward trunk posture and lower velocities. Increasing mechanization invites more research on the exposures associated with machinery operation and increasing automation.